ANALISIS AKAD IJARAH DALAM PRAKTIK PRODUK PEMBIAYAAN LEMBAGA KEUANGAN DI INDONESIA (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2022)
This study aims to explain how Indonesian financial institutions apply ijarah applications to financial products.This study uses a descriptive analysis method to explain the concept of Islamic banks regarding al-Ijarah as a general lease, but the difference with Islamic banks is the lease that the customer can choose at the end of the contract. The results of this study indicate that Islamic banks and financial companies that borrow various financial products consistently exempt them from being prohibited by religious law. This indicates compliance with all applicable regulations, regardless of what is required by law by Government Agencies, DSN-MUI or Ulama Majma`al-Fiqh al-Islami. The results of this study are able to provide an overview to Islamic Financial Institutions both Bank and Non-Bank to always pay attention to the Ijarah services and processes offered to customers to create customer satisfaction.